Financial inclusion around the world: progress and challenges (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
Financial inclusion is becoming a priority for many national governments and international institutions across the world, mainly because of its potential positive influence on the reduction of poverty, and the improvement of economic growth and financial stability. Fortunately, the efforts to increase the level of financial inclusion have started to bear fruit. However, there is still work to be done. This article presents an overview of important issues of financial inclusion, which includes the different dimensions of the concept and its determinants, and recent advances in this field. It also presents some reflections on the main challenges facing public authorities and financial policymakers.
Keywords: Financial inclusion; unbanked; financial exclusion; financial literacy.